Freezing/storing olives, consequences for extra virgin olive oil quality. (October 2019) - Masella, Piernicola; Guerrini, Lorenzo; Angeloni, Giulia; Spadi, Agnese; Baldi, Fabio; Parenti, Alessandro
Highlights: The oils from frozen olive retain the commercial extra virgin grade. A strong reduction of biophenols, but profiles were almost unaffected. A shift of the LOX pathway towards more oxidized compounds. Occurrence of volatiles related to olive deterioration (microbial activity). Kind of initial freezing treatment deserves only minor importance. Abstract: The feasibility of producing extra virgin olive oil several months after the harvest season has been investigated. For this purpose, fresh olive drupes have been frozen by three different methods (i.e. blast freezer, cryogenic nitrogen, and conventional static freezer) and processed to olive oil after 6 months of storage at −25 °C temperature. The quality of the oils extracted from the frozen olive has been compared to a control olive oil produced from the corresponding fresh olive drupes, without freezing or storing, and according to the oil conventional commercial parameters (free acidity, peroxide value, UV coefficients), biophenolic and volatile profiles. The oils from frozen olive retain the commercial extra virgin grade despite a slight increment in the peroxide values, regardless the initial freezing treatment. A strong reduction of biophenols has been recorded, without significant differences imputable to the initial freezing method. However, the biophenolic profiles were almost unaffected, unlike the volatile profiles which undergo two main variations. First, a shift of the LOX pathway towards more oxidized compounds, such as hexanal and hexan-1-ol. Second, the occurrence of volatiles generally related to olive deterioration as response to microbial activity and/or amino acid conversion, such as butyl acetate, 3-methyl butanol and ethyl propanoate. This effect seems to be more intense when the initial freezing was performed by the conventional static freezer. An olive sanification treatment could be implemented before freezing to face this problem.